Pengembangan E-Module Materi Manajemen Perawatan Gedung Dan Pemeliharaan Komponen Arsitektural Dan Struktural - Sheshe Leafhayati Rusdi; Anisah Anisah; Tuti Iriani (Journal of Innovative and Creativity, 2025)
The research aims to develop an E-Module for the subject of building maintenance management and the maintenance of architectural and structural components within the Building Engineering Education Major, Faculty of Engineering, Jakarta State University. The method used was Research and Development (R&D), adopting the Four-D (4D) development model, which consists of four stages define, design, development, and dissemination. The validation results from building maintenance experts yielded an average score of 77,33 classified as ‘Feasible’, with a validity score of 0,72 which categorized as 'Valid'. The media expert’s validation yielded an average score of 87,50 classified as 'Highly Feasible', with a validity score of 0,97 which categorized as 'Highly Valid'. The language expert’s validation yielded an average score of 88,00 also classified as 'Highly Feasible', with a validity score of 0,97 which categorized as 'Highly Valid'. In addition, the average pre-test score was 68 points, and the post-test score was 82 points. The N-Gain test results showed a score of 0,43 classified as "Effective" category. Based on the expert validation and the N-Gain test results, it can be concluded that this Building Maintenance E-Module is highly feasible and effective for use in building maintenance courses.